Tryptophan-Degrading Enzymes in Tumoral Immune Resistance - van Baren, Nicolas; Van den Eynde, Benoît J. (Frontiers in Immunology, 2016)
Tryptophan is required for T lymphocyte effector functions. Its degradation is one of the mechanisms selected by tumors to resist immune destruction. Two enzymes, tryptophan 2,3-dioxygenase (TDO) and indoleamine 2,3-dioxygenase 1 (IDO1), control tryptophan degradation through the kynurenine pathway. A third protein, indoleamine 2,3-dioxygenase 2 (IDO2), was identified more recently. All three enzymes were reported to be expressed in tumors, and are candidate targets for pharmacological inhibition aimed at restoring effective anti-tumoral immunity. In this review, we compare these three enzymes in terms of structure, activity, regulation and expression in healthy and cancerous tissues, in order to appreciate their relevance to tumoral immune resistance.